Tissue expression and sero-reactivity of tumor-specific antigens in colorectal cancer - Gerhardt, Axel; Usener, Dirk; Keese, Michael; Sturm, Jörg; Schadendorf, Dirk; Eichmüller, Stefan B. (Cancer letters, 2004)
The expression of 14 individual and two groups of tumor antigens was characterized for colorectal carcinoma by RT-PCR using 26 colorectal carcinoma specimens, eight cell lines, six samples of patients with inflammatory bowl diseases, and nine specimens from different locations of an individual patient with a metastasized rectal carcinoma. The most frequently detected mRNAs were MAGE-A1 (58%), GAGE-3-7 (54%), and cTAGE-5a (31%). At medium frequencies (12-19%) we found cTAGE-1, MAGE-A2, se57-1, RAGE-4, and GAGE-1,2,8, while other tumor antigens were expressed rarely (<9%). 85% of the samples were positive for at least one of the most frequently expressed antigens. Using a secondary SEREX approach and sera of eight colorectal cancer patients we found reactive antibodies against recombinant cTAGE-1 (2 sera), se57-1 (2), truncated GAGE (1), and MAGE-A1 (1). We conclude that certain cancer-germline genes can be detected in colorectal cancer and might therefore be promising targets for immunotherapy.
Gesehen am 25.11.2020